2006
DOI: 10.1254/jphs.fp0060159
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in the Electrical Field Stimulation-Induced Contractions of Sphincter of Oddi and Gallbladder Strips in Guinea Pigs

Abstract: Abstract. The aim of this study was to investigate the modulatory role of nitric oxide (NO) in the electrical field stimulation (EFS)-induced contractions of isolated sphincter of Oddi (SO) and gallbladder strips from guinea pigs. EFS was used to activate the intrinsic nerves in SO and gallbladder strips. EFS produced frequency-dependent biphasic contractile responses in the SO strips. A smaller contraction, "on response", occurred during EFS, which was followed by a bigger contraction, "off response". Both re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…CCK8 acts presynaptically within gallbladder ganglia to increase the release of acetylcholine from vagal terminals, [8,19] whereas nitric oxide, a primary gas messenger or nerve transmitter, serves as a potent and efficient relaxant of gallbladder smooth muscle in a manner similar to that in other smooth muscles. [20,21] In this study, we observed that MYPT1 also played essential functions in the contractile behaviors of the gallbladder. Deletion of MYPT1 led to dysfunctional motility of the gallbladder.…”
Section: Introductionmentioning
confidence: 67%
“…CCK8 acts presynaptically within gallbladder ganglia to increase the release of acetylcholine from vagal terminals, [8,19] whereas nitric oxide, a primary gas messenger or nerve transmitter, serves as a potent and efficient relaxant of gallbladder smooth muscle in a manner similar to that in other smooth muscles. [20,21] In this study, we observed that MYPT1 also played essential functions in the contractile behaviors of the gallbladder. Deletion of MYPT1 led to dysfunctional motility of the gallbladder.…”
Section: Introductionmentioning
confidence: 67%
“…Parkman et al [12] demonstrated that after CBDL, an inhibitory NO pathway was also activated to help decrease gallbladder contractions in addition to the decreased cholinergic contractions. Recently, Gültekin et al [13] reported that the NOS inhibitor, NOARG, significantly increased the contractions induced by electrical field stimulation, and this increase in the contractions was reversed by L -arginine in guinea pig gallbladder strips in vitro conditions. CBDL causes gallbladder inflammation similar to acute acalculous cholecystitis [11] .…”
Section: Discussionmentioning
confidence: 99%
“…There could also be other mechanisms, of course. For example, nitric oxide also participates in the regulation of SO contractions 35 . The effect of acupuncture on these potential factors remains to be studied.…”
Section: Discussionmentioning
confidence: 99%